Elucidation of direct competition and allosteric modulation of small‐molecular‐weight protein ligands using surface plasmon resonance methods. Issue 8 (12th March 2015) - Huber, Walter; Sinopoli, Alessandro; Kohler, Josiane; Hug, Melanie; Ruf, Armin; Huber, Sylwia
<x xml:space="preserve">Abstract</x> The present work introduces a surface plasmon resonance‐based method for the discrimination of direct competition and allosteric effects that occur in ternary systems comprising a receptor protein and two small‐molecular‐weight ligands that bind to it. Fatty acid binding protein 4, fructose‐1, 6‐bisphosphatase and human serum albumin were used as model receptor molecules to demonstrate the performance of the method. For each of the receptor molecules, pairs of ligand molecules were selected for which either direct competition or an allosteric effect had already been determined by other methods. The method of discrimination introduced here is based on the surface plasmon resonance responses observed at equilibrium when an immobilized receptor protein is brought into contact with binary mixtures of interacting ligands. These experimentally determined responses are compared with the responses calculated using a theoretical model that considers both direct competition and allosteric ligand interaction modes. This study demonstrates that the allosteric ternary complex model, which enables calculation of the fractional occupancy of the protein by each ligand in such ternary systems, is well suited for the theoretical calculation of these types of responses. For all of the ternary systems considered in this work, the experimental and calculated responses in the chosen concentration ratio range were identical within a five‐σ confidence interval when the calculations considered the correct interaction mode of the ligands (direct competition or different types of allosteric regulation), and in case of allosteric modulation, also the correct strength of this effect. This study also demonstrates that the allosteric ternary complex model‐based calculations are well suited to predict the ideal concentration ratio range or even single concentration ratios that can serve as hot spots for discrimination, and such hot spots can drastically reduce the numbers of measurements needed for discrimination between direct competition and distinct modulation modes (neutral, positive or negative allostery). Copyright © 2015 John Wiley & Sons, Ltd.